Associations of Obesity With Growth and Puberty in Children: A Cross-Sectional Study in Fuzhou, China - Ying Zhang; Xin Yuan; XiaoHong Yang; XiangQuan Lin; ChunYan Cai; ShiJun Chen; ZhuanZhuan Ai; HuaKun ShangGuan; WenYong Wu; RuiMin Chen (Frontiers Media S.A., 2023)
Objectives: To investigate the associations of obesity with growth and puberty in children.Methods: From November 2017 to December 2019, height, weight, and Tanner stages of 26,879 children aged 3-18 years in Fuzhou, China were assessed.Results: The obese group was significantly taller than the non-obese group after age 4 years for both genders, yet there was no significant difference in height between obese and non-obese group after 15.5 years old for boys and 12.5 years old for girls. The inflection points of significant growth deceleration in obese and non-obese groups were 14.4 and 14.6 years old for boys, and 11.8 and 12.8 years old for girls, respectively. The proportions of testicular development in boys with obesity and non-obesity were 7.96% and 5.08% at 8.5-8.9 years old, respectively, while the proportions of breast development in girls were 17.19% and 3.22% at age 7.5-7.9 years old, respectively.Conclusion: Children with obesity were taller in early childhood, earlier onset of puberty and earlier cessation of growth than children with non-obesity of the same age. However, there was sex dimorphism on the effect of obesity on the incidence of precocious puberty.